Advances in Technical Diagnostics : Proceedings of the 6th International Congress on Technical Diagnostic, ICDT2016, 12 - 16 September 2016, Gliwice, Poland /: Proceedings of the 6th International Congress on Technical Diagnostic, ICDT2016, 12 - 16 September 2016, Gliwice, Poland. (2017) - Unknown
No abstract available